The Relationship Between Academic Library Department Experience and Perceptions of Leadership Skill Development Relevant to Academic Library Directorship - Harris, Colleen S. (The Journal of academic librarianship, 2015)
Though research into academic library director leadership has established leadership skills and qualities required for success, little research has been done to establish in which library departments library directors were most likely to acquire those skills and qualities. This study surveyed academic library directors at Carnegie-designated Master's granting institutions about their previous academic library positions, and what skills and qualities they perceived to have exercised in those positions. The two research questions addressed by this portion of the research project were: (1) is the perception of library leadership skill and quality development equal across departmental experience? and (2) what are the leadership skills and qualities most commonly perceived to be used in each department? Findings revealed that respondents perceived that there were great opportunities to exercise leadership qualities in previous positions, but few opportunities to develop more empirically measurable leadership skills. In addition, respondents perceived those skill development opportunities to be available only once working in the position of library director or in the administration department of academic libraries.